Socialist religion and the emergence of occultism: a genealogical approach to socialism and secularization in 19th-century France - Strube, Julian (Religion, 2016)
It is often assumed that the history of 19th-century France was determined by a struggle between anti-religious progressive reformers and Catholic reactionaries, culminating in laïcité. In this process, the role of socialism as a secular force is usually taken for granted. This article will argue that a more complex approach to socialism can contribute to a better understanding of secularization and the emergence of “modern” forms of religion. Firstly, it will be discussed that pre-1848 social reformers were highly religious, despite their depiction in historical narratives influenced by Marxism. Secondly, it will be shown that socialist ideas continued, after 1848, in new religious movements. This will be demonstrated on the basis of the intellectual development of the socialist Alphonse-Louis Constant who, under his pen-name Eliphas Lévi, is regarded as the founder of occultism. An analysis of his writings will help to illuminate the ambiguous relationship between socialism and secularization.
Gesehen am 25.07.2017